The African press in South Africa - St Leger, Frederick York (Rhodes University, Faculty of Humanities, Department of Sociology, 1975)
In a plural society, riven by deep conflict, as is South Africa, where however the Press retains a considerable measure of freedom to contribute to the political process it is the political role which is of the greatest significance rather than, for example, the reflection by the Press of social values or the internal organisation of the Press as a social system. Although it is, of course, hardly possible completely to ignore these other aspects in any institutional study.
Keywords: Press -- South Africa -- History; Ethnic press -- South Africa -- History